(untitled) (Hematology Meeting Reports, 2009)
In just the past decade, positron emission tomography with fluorine-18 fluorodeoxyglucose (PET scanning) has come to be considered an essential component of initial staging of Hodgkin’s disease (HD) at many medical centers around the world. In addition, it is common to utilize PET scanning to evaluate response to treatment and to employ it as a component of routine surveillance programs.